The gas-to-extinction ratio and the gas distribution in the Galaxy - Zhu, Hui; Tian, Wenwu; Li, Aigen; Zhang, Mengfei (Monthly notices of the Royal Astronomical Society, 2017)
Abstract We investigate the relation between the optical extinction (A V ) and the hydrogen column density (N H) determined from X-ray observations of a large sample of Galactic sightlines towards 35 supernova remnants, 6 planetary nebulae and 70 X-ray binaries for which N H was determined in the literature with solar abundances. We derive an average ratio of 〈N H/A V 〉 = (2.08 ± 0.02) × 1021 H cm−2 mag−1 for the whole Galaxy. We find no correlation between 〈N H/A V 〉 and the number density of hydrogen, the distance away from the Galactic Centre and the distance above or below the Galactic plane. The 〈N H/A V 〉 ratio is generally invariant across the Galaxy, with 〈N H/A V 〉 = (2.04 ± 0.05) × 1021 H cm−2 mag−1 for the first and fourth Galactic quadrants and 〈N H/A V 〉 = (2.09 ± 0.03) × 1021 H  cm−2 mag−1 for the second and third Galactic quadrants. We also explore the distribution of hydrogen in the Galaxy by enlarging our sample with additional 74 supernova remnants for which both N H and distances are known. We find that, between the Galactic radius of 2 and 10 kpc, the vertical distribution of hydrogen can be roughly described by a Gaussian function with a scaleheight of h = 75.5 ± 12.4 pc and a mid-plane density of n H(0) = 1.11 ± 0.15 cm−3, corresponding to a total gas surface density of ∑gas ∼  7.0 M⊙ pc−2. We also compile N H from 19 supernova remnants and 29 X-ray binaries for which N H was determined with subsolar abundances. We obtain 〈N H/A V 〉 = (2.47 ± 0.04) × 1021 H cm−2 mag−1 which exceeds that derived with solar abundances by ∼20 per cent. We suggest that in future studies one may simply scale N H derived from subsolar abundances by a factor of ∼1.2 when converting to N H of solar abundances.